Iron overload favors the elimination of Leishmania infantum from mouse tissues through interaction with reactive oxygen and nitrogen species. - Sílvia Vale-Costa; Sandra Gomes-Pereira; Carlos Miguel Teixeira; Gustavo Rosa; Pedro Nuno Rodrigues; Ana Tomás; Rui Appelberg; Maria Salomé Gomes (Public Library of Science (PLoS), 2013)
Iron plays a central role in host-parasite interactions, since both intervenients need iron for survival and growth, but are sensitive to iron-mediated toxicity. The host's iron overload is often associated with susceptibility to infection. However, it has been previously reported that iron overload prevented the growth of Leishmania major, an agent of cutaneous leishmaniasis, in BALB/c mice. In order to further clarify the impact of iron modulation on the growth of Leishmania in vivo, we studied the effects of iron supplementation or deprivation on the growth of L. infantum, the causative agent of Mediterranean visceral leishmaniasis, in the mouse model. We found that dietary iron deficiency did not affect the protozoan growth, whereas iron overload decreased its replication in the liver and spleen of a susceptible mouse strain. The fact that the iron-induced inhibitory effect could not be seen in mice deficient in NADPH dependent oxidase or nitric oxide synthase 2 suggests that iron eliminates L. infantum in vivo through the interaction with reactive oxygen and nitrogen species. Iron overload did not significantly alter the mouse adaptive immune response against L. infantum. Furthermore, the inhibitory action of iron towards L. infantum was also observed, in a dose dependent manner, in axenic cultures of promastigotes and amastigotes. Importantly, high iron concentrations were needed to achieve such effects. In conclusion, externally added iron synergizes with the host's oxidative mechanisms of defense in eliminating L. infantum from mouse tissues. Additionally, the direct toxicity of iron against Leishmania suggests a potential use of this metal as a therapeutic tool or the further exploration of iron anti-parasitic mechanisms for the design of new drugs.